Social Constructionism of Corporate Discourse - I. P. Romashova (Научный диалог)
The article is devoted to the problem of social constructionism of modern discourses, which is manifested in their ability to form the opinion of target groups and create algorithms of social actions. The existing approaches to the understanding of social constructionism, indicating the possibility of linguistic interpretation and modelling technologies for creating discursive models and their inclusion in the activities of social groups, one of which is the corporation, are considered. The novelty of the study is seen in the fact that for the first time the concept of “discursive technology” is considered as an object of study in linguistics, characterizing social constructionism. A typology of discursive technologies of construction, including technologies of text construction, text development and its implementation in professional practices of corporates is proposed. The author uses the method of complex pragmastylistic analysis of texts in corporate discourse and reconstructs the discursive technologies of text construction and the formation of communicative skills of staff.